2020
DOI: 10.3389/fpsyg.2020.596206
|View full text |Cite
|
Sign up to set email alerts
|

Work Fatigue Profiles: Nature, Implications, and Associations With Psychological Empowerment

Abstract: The present study examined the distinct configurations, or profiles, taken by work fatigue dimensions among samples of military (n = 1,436) and civilian (n = 2,477) employees. We also tested profile similarity across these two samples of employees. In addition, this research documented the relations between the identified work fatigue profiles, one predictor variable (psychological empowerment), and a series of attitudinal outcomes (job satisfaction, career satisfaction, and turnover intentions) among military… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 98 publications
0
5
0
Order By: Relevance
“…In the male sex, the endurance of the body will be stronger than that of the female [16]. This statement is directly proportional to the theory that men's endurance is stronger than that of women [17]. Compared with the results of the author's research now, results were found that were in line with the theory, namely the majority of male workers were 29 people and 7 other people with the female sex.…”
Section: B Gendermentioning
confidence: 56%
“…In the male sex, the endurance of the body will be stronger than that of the female [16]. This statement is directly proportional to the theory that men's endurance is stronger than that of women [17]. Compared with the results of the author's research now, results were found that were in line with the theory, namely the majority of male workers were 29 people and 7 other people with the female sex.…”
Section: B Gendermentioning
confidence: 56%
“…Work fatigue is composed of three different levels of fatigue: emotional, mental, and physical fatigue and may affect psychological and physical health of the workers leading to less efficient work recovery and negative work attitude. [34]. Therefore, an adequate physical demand is fundamental to preserve the mental state of the worker.…”
Section: Discussionmentioning
confidence: 99%
“…Participant's levels of mental (six items; e.g., "Actually, I want to mentally shut down"; α = .94) and emotional (six items; e.g., "Actually, I want to avoid anything that took too much emotional energy"; α = .95) fatigue were measured at all occasions using the Work Fatigue Inventory (Frone & Tidwell, 2015; French version by Blais et al, 2020). Following Barling and Frone (2017), we rely on a global score of fatigue (α = .96).…”
Section: Fatigue (Outcome)mentioning
confidence: 99%